Optimization of Pangasius Catfish Production in Pagersari Village, Tulungagung Regency - Mochammad Fattah; Susadiana Susadiana; Dwi Sofiati (Journal of Aquaculture and Fish Health, 2021)
Pangasius catfish is freshwater fish for consumption that can be cultivated through fish farming. In order to produce optimal profits, Pangasius catfish farming must pay attention to the use of inputs in the form of seeds, feed and electricity. The purpose of this study was to analyze the optimization of Pangasius catfish production in Tondo Lestari fish cultivator group, Pagersari Village, Tulungagung Regency. Data collection techniques were in the form of interviews, observation and documentation. The data analysis used was linear programming using the POM-QM  for Windows 5 software tool. The Pangasius catfish farming activities of the Tondo Lestari fish cultivator group have been optimal because they resulted in a low production difference between factual and optimal conditons of 3,05 kg or a profit of Rp. 10,502. . The optimal production of Pangasius catfish in a pond size of 200 m2 was 3,173.21 kg and the optimal production in a pond size of 300 m2 was 4,839.83 kg. Therefore,  it can be concluded that Pokdakan Tondo Lestari can take advantage of additional feed and electricity input by reducing the use of seed input by 1.487 heads to increase profits.